2011
DOI: 10.4028/www.scientific.net/amr.217-218.1584
|View full text |Cite
|
Sign up to set email alerts
|

Crush Behavior of Corrugated Cores Sandwich Panels

Abstract: The out-of-plane quasi-static compressive behavior of four types of corrugated cores (V-type, U-type, X-type and Y-type core) has been investigated by experiment and FE simulations. By transient dynamic finite element analysis code MSC.Dytran numerical simulations were performed for calculating crushing forces, deformation mode and energy absorption. The FE simulations predict the crush behavior of cores with reasonable accuracy and provide the whole progressive buckling process and deformation modes. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The specific energy absorption of the tested single-layer corrugated core at quasi-static strain rate varies between 0.4 and 0.61 kJ kg −1 at nominal strain of 0.57 corresponding to the displacement of abrupt increase in load values. These energy absorption values are comparable, by taking into account the densification strains, with the specific energy absorptions of mild steel V-, U-, X- and Y-type core structures varying between 0.94 and 4.04 kJ/kg, at the final strains between 0.66 and 0.85 [18]. The specific energy absorption of the tested corrugated structure increased to 1.31 kJ kg −1 when the final strain increased to 0.66.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific energy absorption of the tested single-layer corrugated core at quasi-static strain rate varies between 0.4 and 0.61 kJ kg −1 at nominal strain of 0.57 corresponding to the displacement of abrupt increase in load values. These energy absorption values are comparable, by taking into account the densification strains, with the specific energy absorptions of mild steel V-, U-, X- and Y-type core structures varying between 0.94 and 4.04 kJ/kg, at the final strains between 0.66 and 0.85 [18]. The specific energy absorption of the tested corrugated structure increased to 1.31 kJ kg −1 when the final strain increased to 0.66.…”
Section: Resultsmentioning
confidence: 99%
“…V-frame corrugated structures were shown to be more inertia sensitive than Y-frame, as the deformation in V-frame structure is the stretching governed buckling, while in Y-frame core it proceeds with the bending of one of the legs [4]. It was also shown that U-, X- and V-frame cores exhibiting buckling mode of deformation showed higher crushing strengths and energy absorptions than Y-frame cores exhibiting the bending mode of deformation [18]. The sandwich panels constructed using the periodic cellular metal constructions are attractive both for the impact load mitigation such as blast loading, where the large amount of blast energy is required to be absorbed by the progressive crushing of the core, and for the heat exchange media, where the heat dissipation is request in a relatively small space [1].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with foam sandwich panel, honeycomb sandwich panel and lattice sandwich panel, corrugated sandwich panel has higher bending, shear and torsion resistances [8]. The corrugated core can be in different shapes, such as triangular [9], trapezoidal [10,11], curvilinear [12], sinusoidal [10], V-shape, U-shape, X-shape, and Y-shape [13], etc. The geometric configuration has a significant influence on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Core materials are subjected to shear loads and compression loads in the sandwich structure, examples of these materials and structures, depending on the application, are metal or polymeric foams, honeycomb structures, cork, and even corrugated cores [11][12][13][14][15][16][17]. Foams are characterized by low densities, from polymeric foams such as polyvinyl chloride (PVC), polymethacrylimide (PMI), expanded polystyrene (EPS), and polyurethane (PU) to phenolic resin-based foams.…”
Section: Introductionmentioning
confidence: 99%